The Effect Of Social Media Marketing Instagram and Price On Purchasing Decisions @Rumahbatik.Palbatu - Aldrich Atha Rheza Hariyanto; Btari Mariska Purwaamijaya; Adam Hermawan (Indonesian Journal of Digital Business, 2024)
This study examined the influence of marketing through Instagram social media and price on consumer purchasing decisions at Rumah Batik Palbatu. In the context of the local batik business in Indonesia, especially facing price competition with Chinese batik imports, Rumah Batik Palbatu faces the challenge of significant sales fluctuations. Therefore, this study aims to provide in-depth insight into how marketing through Instagram social media and product prices can influence consumer purchasing decisions. This study uses a descriptive method with a quantitative approach. The data sampling technique used is probability sampling with a simple random sampling technique, and the data obtained are processed using multiple linear regression analysis techniques. The results of this study include: (1) SPSS analysis shows that social media marketing has no significant effect on purchasing decisions at Rumah Batik Palbatu, with a partial test value of 0.400 and a significance probability of 0.690, rejecting H1 and accepting H0; (2) Price has a positive and significant influence on purchasing decisions at Rumah Batik Palbatu based on the results of the analysis using SPSS 27, with a t-value of 4.029 and a significance probability of 0.00, which indicates that the alternative hypothesis (H2) is accepted, and the null hypothesis (H0) is rejected; (H3) Social media marketing and price simultaneously have a positive and significant influence on purchasing decisions at Rumah Batik Palbatu MSMEs, which is supported by the results of the F test with a simultaneous test value of 31.276 and a significance probability of 0.001.